2001
DOI: 10.1128/jcm.39.2.636-641.2001
|View full text |Cite
|
Sign up to set email alerts
|

Analysis for a Limited Number of Gene Codons Can Predict Drug Resistance of Mycobacterium tuberculosis in a High-Incidence Community

Abstract: Correct and rapid diagnosis is essential in the management of multidrug-resistant tuberculosis (MDR-TB).In this population-based study of 61 patients with drug-resistant tuberculosis, we evaluated the frequency of mutations and compared the performance of genotypic (mutation analysis by dot blot hybridization) and phenotypic (indirect proportion method) drug resistance tests. Three selected codons (rpoB531, rpoB526, and katG315) allowed identification of 90% of MDR-TB cases. Ninety percent of rifampin, strepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
123
6

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(145 citation statements)
references
References 21 publications
16
123
6
Order By: Relevance
“…This is in agreement with the results published earlier [9,10]. In addition, our observation that Isoniazid resistance was most commonly associated with katG mutation was similar to the one reported earlier [11].…”
Section: Discussionsupporting
confidence: 83%
“…This is in agreement with the results published earlier [9,10]. In addition, our observation that Isoniazid resistance was most commonly associated with katG mutation was similar to the one reported earlier [11].…”
Section: Discussionsupporting
confidence: 83%
“…However, the molecular mechanism(s) of drug resistance in a number of clinical isolates are as yet unknown and molecular prediction for drug resistance is optimal for RIF-resistance, where approximately 98% of RIF-resistant clinical isolates have a mutation in the rpoB gene (Table 1). Compiling evidence from these studies indicated that drug-resistant isolates are frequently mutated at certain codons (e.g., association between katG315 and INH resistance) and that these codons should be the initial focus for molecular prediction of drug resistance in M. tuberculosis (36). Although numerous studies have shown associations between different mutations and drug resistance (see references in Table 1), there are limited data showing that not all mutations identified are the causative mechanism of drug resistance.…”
Section: Mechanismsmentioning
confidence: 99%
“…7,8 M. ulcerans strains expressing phenotypic and genotypic resistance were generated under RMP monotherapy in a mouse model, but systematic drug resistance surveillance in clinical M. ulcerans strains has not yet been conducted. 16 To obtain baseline data on resistance to RMP and SM in Ghana, we screened clinical M. ulcerans isolates obtained from BUD patients treated by surgery and/or antimycobacterial drugs.…”
Section: Discussionmentioning
confidence: 99%
“…6 Genotypic drug-resistance testing constitutes a reliable and expedient alternative to predict phenotypic drug resistance of M. tuberculosis to RMP and SM. 7,8 In 2007, WHO also emphasized the importance of systematic global drug resistance surveillance for leprosy and implemented a genotypic drug-resistance surveillance system in 2009. So far, high concordance between conventional drug-susceptibility testing (mouse footpad technique) and DNA sequencing methods has been observed.…”
Section: Introductionmentioning
confidence: 99%